Forming History, Inhabiting Form in Marvell's "Upon Appleton House". - Shohet, Lauren (Poetics Today)
Andrew Marvell's "Upon Appleton House" meditates on when and how forms and events become meaningful. The poem reveals the limitations of criticism that assumes rather than questions what constitutes history. Drawing on the literary-historical conventions of its inherited country house form while also engaging its immediate historical context of 1651 northern England, "Upon Appleton House" offers a dynamic, relational model of how history, form, and interpretation articulate one another's conditions of possibility. This suggests that criticism should acknowledge form as an element of history: that we should understand forms as hermeneutic and heuristic practices that can influence historical experience in addition to recording or mediating it. The poem's multiple time scales--which range from topical political crisis, to multigenerational dynastic heritage, to the life spans of birds and trees, to apocalyptic temporality--render history polychronic: individual moments achieve full historical significance when superimposed upon one another. The allegories of relationships between readers and the things they read in "Upon Appleton House" limn a contingent, supple interpretive practice charged with linking plural histories and textualities without reducing any to a mere index, foreshadowing, or figure of another. Reading forms in multiple ways and considering individual moments as intersections of different historical frameworks complicates relationships between history and literary history.